PENGARUH MEDIA SOSIAL DALAM PEMBENTUKAN KARAKTER DIGITAL PADA REMAJA - Salsa Nabila Azzahra; Edy Soesanto (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Education is an important thing that cannot be ignored throughout human life. In the current digital era, character education is very important to be implanted and taught massively to students. The aim of this research is to explore the importance of character education in learning to improve the quality of education in the digital era. The research method used is literary research. Literary research is a research method carried out using collect data and take notes, evaluate documents or reading. Literary research can be obtained from various sources such as books, magazines, internet, libraries and documents. We hope that the results of this research can provide encouragement to all parties, including educational institutions, families and society, so that this can be done on a large scale to help make character education teachable and achievable, giving birth to a generation of people with personality and playing a role in improving the quality of education in the digital era.